Axial slicing versus bivalving in the pathological examination of pancreatoduodenectomy specimens (APOLLO): a multicentre randomized controlled trial. Issue 9 (September 2021) - van Roessel, Stijn; Soer, Eline C.; van Dieren, Susan; Koens, Lianne; van Velthuysen, Marie Louise F.; Doukas, Michael; Groot Koerkamp, Bas; Fariña Sarasqueta, Arantza; Bronkhorst, Carolien M.; Raicu, G. Mihaela; Kuijpers, Karel C.; Seldenrijk, Cornelis A.; et al.
Abstract: Background: In pancreatoduodenectomy specimens, dissection method may affect the assessment of primary tumour origin (i.e. pancreatic, distal bile duct or ampullary adenocarcinoma), which is primarily determined macroscopically. This is the first study to prospectively compare the two commonly used techniques, i.e. axial slicing and bivalving. Methods: In four centres, a randomized controlled trial was performed in specimens of patients with a suspected (pre)malignant tumour in the pancreatic head. Primary outcome measure was the level of certainty (scale 0–100) regarding tumour origin by four independent gastrointestinal pathologists based on macroscopic assessment. Secondary outcomes were inter-observer agreement and R1 rate. Results: In total, 128 pancreatoduodenectomy specimens were randomized. The level of certainty in determining the primary tumour origin did not differ between axial slicing and bivalving (mean score 72 [sd 13] vs. 68 [sd 16], p = 0.21), nor did inter-observer agreement, both being moderate (kappa 0.45 vs. 0.47). In pancreatic cancer specimens, R1 rate (60% vs. 55%, p = 0.71) and the number of harvested lymph nodes (median 16 vs. 17, p = 0.58) were similar. Conclusion: This study demonstrated no differences in determining the tumour origin between axial slicing and bivalving. Both techniques performed similarly regarding inter-observer agreement, R1 rate, and lymph node harvest.